Effect of α-galactosidase Supplementation in Diet on Egg Production, Egg Quality and Dietary Digestibility of Laying Hens - Harnkaew, Chonladda; Bunchasak, Chaiyapoom; Rakangthong, Choawit; Sukontasing, Sirapan; Poeikhampha , Theerawit (International Journal of Poultry Science, 2018)
Background and Objective: The carbohydrates in soybean meal consist of approximately 10% oligosaccharides and are linked by an α-1,6 galactosidase bond which cannot be broken down in the small intestine of monogastric animals due to the absence of endogenous α-1,6 galactosidase. This experiment was conducted to determine the effect of α-galactosidase supplementation in the laying hen diet on egg performance, egg quality and dietary digestibility. Methodology: A total of 576 Lohmann brown-classic hens (28 weeks old) were divided into 3 groups of 8 replications with 24 hens each. This experiment design was completely randomized design and there were 3 experimental diets, (1) Positive control diet, (2) Positive control diet decreased by 88 kcal kg–1 ME and supplemented with α-galactosidase at 0.022 and (3) Positive control decreased by 88 kcal kg–1 ME without any supplementation of α-galactosidase (negative control). Results: At the end of the 16 weeks of feeding trial, using α-galactosidase significantly improved egg production (p<0.05), egg mass (p<0.05), feed conversion ratio (FCR, p<0.01) and feed cost per egg (p<0.05), similar to the positive control. Feeding with α-galactosidase significantly improved the specific gravity (p<0.01), shell thickness (p<0.05), eggshell weight (<0.05) and tended to improve dietary digestibility (p<0.10) and decrease retention time in the gastro-intestinal tract (p<0.05). In addition, the apparent metabolizable energy (AME) increased (p<0.01) by α-galactosidase when compared to the negative control. However, the dietary treatment did not influence the other parameters of egg quality and feces score. Conclusion: Supplementation of α-galactosidase with reducing the metabolizable energy improved egg production performance, egg quality and feed digestibility.